Canadian energy efficiency outlook : a national effort for tackling climate change - Langlois, Pierre (Writer on energy efficiency); Gauthier, Genevieve (Gistrup, Denmark : River Publishers, 2020)
Energy Efficiency (EE) has been recognized since the early 1970s as the most relevant mechanism to optimize the way we meet our energy needs. The rationale behind this book is to present where the Canadian EE sector stands today to all Canadian stakeholders and those interested around the world. The Canada Energy Efficiency Outlook aims to outline the different environments that support EE development in our highly diversified provinces and territories, as well as at the national level, and consequently allow the reader to better understand the complexities involved. More globally, this book serves as an important reference for all interested parties on how Canada has variably innovated and developed mechanisms to achieve the goal of making this country more energy efficient.
Federal Review. Provincial and Territories Reviews. Specific Thematic Reviews. Innovative Initiatives.
OCLC-licensed vendor bibliographic record.
Keywords: Power resources -- Canada -- Forecasting; Energy policy -- Canada; BUSINESS & ECONOMICS / Project Management; TECHNOLOGY / Power Resources